2022
DOI: 10.3389/fpsyg.2022.779905
|View full text |Cite
|
Sign up to set email alerts
|

Lexical Orthographic Knowledge Mediates the Relationship Between Character Reading and Reading Comprehension Among Learners With Chinese as a Second Language

Abstract: Reading in Chinese is complex because readers should not only recognize characters by basic units (i.e., characters) but also integrate characters into words when reading text. While many efforts have been devoted to investigating the effect of sub-lexical orthographic knowledge in Chinese character reading, less is known about the role played by lexical orthographic knowledge at word level. A total of 424 secondary learners with Chinese as a second language (CSL) in Hong Kong were assessed with character read… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Therefore, proficient orthographic awareness of the constituent components helps readers recognize the sound and meaning of Chinese characters (Liao et al, 2022) and thus to specify and manipulate the sublexical representation of a Chinese character. Empirical evidence showed that young children with better orthographic awareness have remarkable performance in Chinese word reading (e.g., Li et al, 2012;Yeung et al, 2016).…”
Section: Lexical Processes In the Chinese Lexiconmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, proficient orthographic awareness of the constituent components helps readers recognize the sound and meaning of Chinese characters (Liao et al, 2022) and thus to specify and manipulate the sublexical representation of a Chinese character. Empirical evidence showed that young children with better orthographic awareness have remarkable performance in Chinese word reading (e.g., Li et al, 2012;Yeung et al, 2016).…”
Section: Lexical Processes In the Chinese Lexiconmentioning
confidence: 99%
“…For example, the phonological component “由” /yau4/ gives the hint to the sound of the character “油” /yau4/ (meaning oil), but the character “迪” /dik6/ (meaning enlighten) is pronounced entirely differently even with the same phonetic component. Therefore, proficient orthographic awareness of the constituent components helps readers recognize the sound and meaning of Chinese characters (Liao et al, 2022) and thus to specify and manipulate the sublexical representation of a Chinese character. Empirical evidence showed that young children with better orthographic awareness have remarkable performance in Chinese word reading (e.g., Li et al, 2012; Yeung et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%